Role of Cone-Beam CT in the Intraprocedural Evaluation of Chemoembolization of Hepatocellular Carcinoma. (19th March 2021) - Orlacchio, Antonio; Roma, Silvia; dell'Olio, Vito; Crociati, Sara; Lenci, Ilaria; Francioso, Simona
Abstract : Purpose . To assess the ability of Cone-Beam CT (CBCT), performed during the Transcatheter Arterial Chemoembolization (TACE), in predicting the response to treatment of hepatocellular carcinoma (HCC). Materials and Methods . We evaluated fifty patients (M/F = 40/10, mean age: 66.7 years ± 8.22) with hepatocellular carcinoma (HCC), for a total of 82 nodules evaluated (mean diameter: 21.4 ± 11 mm). All patients performed a CT scan one month before and one month after TACE. After TACE is completed, a CBCT was performed to assess the degree of drug retention in the lesions. For each lesion, the major diameter, volume, and density of the vital portion were evaluated. The response to TACE was assessed using the mRECIST criteria on the CT scan carried out one month after the procedure. The receiver operating characteristic (ROC) curves were performed to assess the accuracy of the CBCT in predicting the response to treatment and to identify the cut-off points for each parameter under examination. Results . A complete response (CR) was observed in 24/50 patients (48%), a partial response (PR) in 16/50 (32%), stable disease (SD) in 8/50 (16%), and progressive disease (PD) in 2/50 (4%). Evaluation of the area under the ROC curve showed that the diameter, volume, and density of the lesion, measured with CBTC, had an accuracy of 94%, 96%, and 98%, respectively, in discriminating a complete response from a not complete response. Conclusion . CBCT is effective in predicting short-term response at 1-month follow-up of HCC treated by chemoembolization.